Indonesia : Implementation of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses implementation of the International Organization of Securities Commissions (IOSCO) objectives and principles of securities regulation in Indonesia. The Capital Markets and Financial Institutions Supervisory Agency (BAPEPAM-LK) has taken impressive steps to increase the transparency of regulation and to institute a comprehensive operational program that meets international norms and Indonesia's understanding of best practices. This paper reveals that the regulatory framework, regulatory powers, and requirements pertaining to the securities regulator are highly transparent. The roles of the regulators and supervisors are also clearly defined.